Expression profiles of microRNAs in midbrain of MPTP-treated mice determined by microRNA sequencing. (25th September 2022) - Liu, Xiaoni; Qi, Yue; Zhao, Guojian; Zhang, Ziwei; Cao, Yidi; Li, Yanning; Xue, Jinhua; Tang, Xiaolu
Highlights: RNA sequencing identified 43 differentially expressed microRNAs in the ventral midbrain of MPTP-induced subacute PD mouse 24 h after modeling. Differenttially expressed miRNAs in the ventral midbrain of MPTP-treated mice were significantly enriched in axon guidance/neuron projection, metabolic pathway and PI3K/AKT signaling pathway, which were involved in the occurrence and development of early PD. Targeted regulation of these differenttially expressed miRNAs may reverse the neurodegeneration of early PD. Abstract: MPTP models have been developed to mimic human Parkinson's disease and serve as an indispensable tool for studying PD. Among them, subacute MPTP PD models are popular due to their short modeling period and similarity to PD pathology. However, the early pathophysiological mechanism of the model remains to be further clarified. More and more studies have shown that dysregulation of miRNAs plays an important role in the occurrence and development of neurodegenerative diseases, including PD. In this study, we identified 43 differentially expressed microRNAs (miRNAs) in the ventral midbrain of MPTP-induced subacute PD mouse by RNA sequencing. Further bioinformatics analysis revealed that these miRNAs were significantly enriched in axon guidance/neuron projection, metabolic pathways/cellular macromolecule metabolic process and PI3K/AKT signaling pathways, which were involved in the occurrence and development of early PD. Thus, targeted regulation of these miRNAs may reverse the neurodegeneration of early PD.